Supporting young learners’ vocabulary through pictures: an action research approach = Hỗ trợ việc học từ vựng của học sinh bằng tranh ảnh - Dương, Thu Trang (2020)
Vocabulary is one the most important elements in English acquisition. Without words, human cannot express their ideas, feelings or thoughts. In the chosen English center in Hanoi, teaching and learning is paid attention to with a view to improve the students‟ English acquisition and one of the major concern here is vocabulary teaching and learning through images of young learners. To explore how images support young learners‟ vocabulary acquisition, the study was carried out among forty 2th grade students for eight weeks with six units in their books. They were divided equally into two groups and each one was taught in two different ways of vocabulary teaching: one with traditional method –the translation method while the other by using pictures. The classroom observations and tests were instruments to collect the data for the research. After the treatment time, the results showed that the experimental group gained higher scores by using pictures to learn vocabulary and the classroom atmosphere was veycomfortable and ludic while the control group obtained not as good results as the experimental one. It can be inferred from the results that images make a greater dedication to enhancing not only young learners‟ vocabulary acquisition but also their motivation in English learning than not using them